A social practice theory of learning and becoming across contexts and time - Penuel, William R.; Van Horne, Katie; DiGiacomo, Daniela; Kirshner, Ben (Frontline Learning Research, 2016)
This paper presents a social practice theory of learning and becoming across contexts and time. Our perspective is rooted in the Danish tradition of critical psychology (Dreier, 1997; Mørck & Huniche, 2006; Nissen, 2005), and we use social practice theory to interpret the pathway of one adolescent whom we followed as part of a longitudinal study of interest-related learning. A social practice theory calls out the ways people pursue diverse concerns, become aware of new possibilities for action as they move across settings of practice, and learn as they adjust contributions to the flow of ongoing activity and to fit demands and structures of local institutions. It also highlights the ways that existing institutional structures of practice frame the choices people make about how and where to participate in activities. This perspective on learning is potentially transformative, in that it provides a way to promote equity by surfacing issues associated with linkages among settings of practice, networks of actors who support persons’ movement across settings, and diversities in structures of practices that shape opportunities to learn and become.